An Interdisciplinary Approach to Software Engineering Teaching: An Experience Report - Braga e Silva, Gláucia; Barbosa, Daniel Mendes; Silva, Fabrício A. (Anais do Workshop sobre Educação em Computação (WEI); 2018: Anais do XXVI Workshop sobre Educação em Computação, 2018)
This work presents the report of an interdisciplinary approach for teaching Software Engineering that involves four related disciplines: Software Engineering II, Software Architecture, Database Systems, and Object-Oriented Programming. The approach was conducted through an specific methodology in which students were grouped together and had to assume roles and responsibilities in the scope of each discipline. In addition, computational tools were used to support collaborative tasks and evaluation and monitoring mechanisms were also included. This interdisciplinary approach was adopted in a Computer Science major course during 2015 and 2016. The results reveal positive impacts in motivation, as well as in learning aspects of the involved students.